2003
DOI: 10.1046/j.1365-2486.2003.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Six years of in situ CO2 enrichment evoke changes in soil structure and soil biota of nutrient‐poor grassland

Abstract: Nutrient‐poor grassland on a silty clay loam overlying calcareous debris was exposed to elevated CO2 for six growing seasons. The CO2 exchange and productivity were persistently increased throughout the experiment, suggesting increases in soil C inputs. At the same time, elevated CO2 lead to increased soil moisture due to reduced evapotransporation. Measurements related to soil microflora did not indicate increased soil C fluxes under elevated CO2. Microbial biomass, soil basal respiration, and the metabolic q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 86 publications
5
75
1
1
Order By: Relevance
“…There are also some inconsistencies in reported responses of soil microbiota to varying CO 2 regimes. Thus, eCO 2 over six growing seasons did not significantly alter soil microbial biomass carbon, metabolic quotient and basal respiration in nutrient-poor grassland [11]; these findings were attributed to nitrogen limitations. However, eCO 2 over five years did not affect microbial biomass, even where nitrogen fertilizer was added [12], suggesting that microbial biomass is insensitive to changes in atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…There are also some inconsistencies in reported responses of soil microbiota to varying CO 2 regimes. Thus, eCO 2 over six growing seasons did not significantly alter soil microbial biomass carbon, metabolic quotient and basal respiration in nutrient-poor grassland [11]; these findings were attributed to nitrogen limitations. However, eCO 2 over five years did not affect microbial biomass, even where nitrogen fertilizer was added [12], suggesting that microbial biomass is insensitive to changes in atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 77%
“…Litter quality effects on MBC in casts may vary with time; thus, high quality litter (lucerne) gave higher MBC at 14 and 28 days compared to wheat straw, but these amendments did not differ at 7 and 56 days [35]; data here for very recent casts showed higher respiration with better quality litter but in later soil aggregates these differences were inconsistent. Given the effects of eCO2 on N concentrations, a reduced microbial community might have been expected; other studies [11] have attributed the absence of any eCO2 effect on MBC in grassland soils to N limitation. If N is a key determinant of MBC responses to eCO2 [14], in our study, some variation between species in microbial eCO2 responses might have been expected given their very different litter N contents; only species' differences were observed and then only in casts.…”
Section: Discussionmentioning
confidence: 99%
“…Carney and Matson (2005) found that plant diversity had a significant effect on microbial community composition through alterations in microbial abundance rather than community composition. Other studies also reported that aboveground net primary productivity was expected to increase soil carbon input through enhancing the turnover of plant biomass and enhancing root exudation and may therefore influence carbon-limited microbial communities in the soil (Niklaus et al 2003;Zak et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the response of microbial communities to environmental change will depend on the time of year. Seasonal variation in the traits of the microbial community could alter its response to environmental change (Bardgett et al, 1999;Niklaus et al, 2003;Cregger et al, 2012). Third, season-dependent responses will be particularly strong when the environmental parameter also varies seasonally.…”
Section: Introductionmentioning
confidence: 99%